Loricaseius lepontinus gen. nov., sp. nov., a new genus and species of eviphidid mite from the Italian Alps (Acari: Mesostigmata), with an updated key to European genera of the family Eviphididae - Plumari, Massimo; Mašán, Peter (Zootaxa, 2014)
A new monotypic genus and a new free-living edaphic species of the family Eviphididae, Loricaseius lepontinus gen. nov., sp. nov., are described on the basis of adults and deutonymphs collected from litter detritus in the Italian Lepontine Alps (Piemonte, Val d’Ossola). The new genus is characterized by a widened and truncate idiosomal vertex with widely spaced setae j2, peritrematal shields extensively expanded laterally in adult stages, narrowed intercoxal region, tarsus I dorsally concave, and strong sexual dimorphism of some secondary sexual characters (dorsal sculpture, posteroventral sclerotization of soft integument, shape of anal shield, opisthogastric and posterodorsal chaetotaxy). Also, the female’s anal shield is surrounded by a large area of strongly sclerotized skin that resembles a ventri-anal shield, with well-developed anterolateral extensions projecting between the dorsal and peritrematal shields, and posteriorly and laterally fused with the dorsal shield. We show that this may be an unusual type of age-related secondary sclerotization unknown in the family. An updated key to European genera of the family is presented.